Análise das variações de precipitação na região hidrográfica do alto Paranapanema (UGRH-14) nos verões de 2001 a 2013 - Pedrozo, Aline Kriss Magalhães [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Studies the precipitation amount that a certain location records is important for analyze factors that somehow affect the population living there, like, for instance, water shortage, floods, and others. The summer of 2013/2014 was one of the driest ever record in São Paulo State. From the water shortage scenario configuration, the aim of this work was estimate the accumulated precipitation rate in the period in the hydrographical region of Alto Paranapanema (UGRHI-14), important agricultural and hydroelectrically centers of São Paulo State. One form to estimate the amount of precipitation in certain location is using data collected by satellites, being the TRMM (Tropical Rainfall Measuring Mission) used in this study. Using Geographical Information Systems (GIS), precipitation rates were mapped using geostatistical techniques. The results were compared with the last 11 years average to verify possible impacts in the deacreasing precipitation rates in the spatial organization of the region. The percentual differences in the precipitation rates vary from -35% to +15% in certain regions. It was observed that the year of 2013 got the lowest preciptation rate among its eleven previous years, the east area was in the most critical sitiation on the aspect of water scarcity

Estudar e analisar a quantidade de precipitação que um determinado local registra é importante para análises de fatores que afetam de alguma forma a população que ali reside como, por exemplo, a escassez de água, enchentes, entre outros. O verão de 2013/2014 foi um dos mais secos dos últimos 50 anos no Estado de São Paulo. Frente ao cenário de escassez hídrica que se caracterizou, o objetivo desse trabalho foi estimar a quantidade de precipitação acumulada no período na região hidrográfica do Alto Paranapanama (UGRHI-14), importante polo agrícola e hidroelétrico do Estado de São Paulo. Uma maneira para estimar a quantidade de precipitação em determinado local é a partir de dados coletados via satélites, sendo que o satélite TRMM (Tropical Rainfall Measuring Mission) foi o utilizado. Através de Sistemas de Informações Geográficas, pretendeu-se mapear os níveis de precipitação e compara-los a média dos últimos 11 anos no período para verificar possíveis impactos da diminuição dos índices pluviométricos na organização do espaço da região. Observou-se que o ano de 2013 recebeu o menor índice de precipitação em relação aos onze anos anteriores, sendo a porção leste a área mais crítica no que diz repeito a escassez de chuva
Keywords: Precipitação (Meteorologia) - Variabilidade - Paranapanema, Rio, Bacia (SP e PR) - 2001-2013; Pluviometros; Satelites meteorologicos; Bacias hidrograficas